A systematic literature review of the impact and measurement of mobility impairment in rare bone diseases - Inês Alves; Ingunn Westerheim; Edward C. Hsiao; Jaymin Upadhyay; Luca Sangiorgi; Alexander Artyomenko; Kim Croskery; Juliet Johns; Emma Warnants; Gabor Barton (Therapeutic Advances in Musculoskeletal Disease)
Background: Although rare bone diseases (RBDs) present mobility challenges, there is little consolidated evidence on evaluated mobility measurement tools or how mobility impairments impact daily activities and quality of life (QoL). Objectives and design: This systematic literature review investigated: (1) the impacts of mobility impairment on daily activities/QoL; (2) the suitability/comprehensiveness of tools measuring mobility. Data sources and methods: MEDLINE/Embase databases (January 19, 2022) and Google (October 19, 2022) were searched for articles published between 2011 and 2022; conference proceedings from 2020 to 2021 were hand-searched. Included articles reported on how mobility impairments impact daily activities/QoL, or the use of tools for measuring mobility, in RBDs. A narrative analysis using descriptive statistics was conducted. Studies were assessed for risk of bias using The Alberta Heritage Foundation for Medical Research Quality Assessment Criteria and National Institute of Health Quality Assessment Tool for Case Series Studies. Results: Inclusion criteria were met by 113 articles, investigating 39 RBDs (sample sizes: N  = 1–959). Mobility impairments, commonly joint function/gait disturbances, negatively impacted daily activities ( n  = 47 cohorts; frequently walking (27/47; 57.4%)) and QoL ( n  = 36 cohorts; commonly pain (30/36; 83.3%; Objective 1). There were 34 functional assessments, 22 questionnaires, and 5 technologies described. Only nine functional assessments/questionnaires were reported to have good validity/reliability/responsiveness for an RBD (not reported for technologies); none comprehensively captured daily living/QoL impacts of mobility impairment. The quality of studies was moderate, though many were case studies/series, which are at inherent risk of bias. Conclusion: Few tools comprehensively captured mobility impairments and associated impacts on daily activities/QoL. Consistent reporting of tools’ validity/reliability/responsiveness would support clinicians in selecting methods for use across RBD populations. Used remotely, wearables could support understanding of real-world mobility challenges. Since searches were conducted, additional technologies (e.g., remote gait analysis) have been tested in RBDs, although validation is required. Protocol PROSPERO registration: CRD42022311513. Sponsored by Ipsen.